Innovation of triangle-shaped plastic bricks: An eco-friendly solution for sustainable community empowerment - Ely Mulyati; Anggi Purnama Sari Dewi; Andrian Noviandry; Hanardono Hanardono (Journal of Community Service and Empowerment, 2025)
This community service activity aims to empower the community in innovative and sustainable plastic waste management. The program is implemented through three main activities, namely socialization of plastic waste management and circular economy, training in making triangular bricks from plastic waste, and creating social media accounts to market Bank Sampah products. The brick-making process involves shredding plastic using a shredder, conducting a sieve analysis to ensure uniform particle size, then mixing it with sand and cement before molding it into a triangular shape. From the initial stage of production, 300 triangular bricks were successfully produced with lightweight and strong characteristics. Through this activity, the community not only gained technical skills but also digital promotion skills to expand their market reach. This program demonstrates that collaboration between universities and the community can yield concrete solutions for plastic waste management while supporting the implementation of a circular economy and sustainable development.